Cardiovascular exercise and motor learning in non-disabled individuals: A systematic review with a behavioral emphasis - Giordano Marcio Gatinho Bonuzzi; Camila Torriani-Pasin (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: This systematic review aimed to investigate the acute effects of cardiovascular exercise on motor learning of non-disabled individuals. Methods: Forty studies were identified through database searching (PsycINFO, CENTRAL, Google Scholar, Scielo, and PUBMED). The studies demonstrated heterogeneity and were classified into two categories to guide the analyses: (1) - studies that investigated the effects of exercise-induced fatigue during practice on the performance in the retention test; (2) - studies that verified the acute impact of the cardiovascular exercise in close temporal proximity to the task practice on motor learning. Results: The studies demonstrated that (1) - the practice under fatigue conditions did not impair motor learning and that (2) - the cardiovascular exercise bout performed in close temporal proximity to task practice enhances the motor learning processes. Conclusion: Cardiovascular exercise enhances motor learning processes; however, these priming effects are dependents on the timing between practice and exercise, type of exercise, and task characteristics.